From one to many: hypertonia in schizophrenia spectrum psychosis an integrative review and adversarial collaboration report - Foucher, Jack R.; Hirjak, Dusan; Walther, Sebastian; Dormegny-Jeanjean, Ludovic C.; Humbert, Ilia; Mainberger, Olivier; de Billy, Clément C.; Schorr, Benoit; Vercueil, Laurent; Rogers, Jonathan; Ungvari, Gabor; Waddington, John; et al. (Schizophrenia research, 2024)
Different types of resistance to passive movement, i.e. hypertonia, were described in schizophrenia spectrum disorders (SSD) long before the introduction of antipsychotics. While these have been rediscovered in antipsychotic-naïve patients and their non-affected relatives, the existence of intrinsic hypertonia vs drug-induced parkinsonism (DIP) in treated SSD remains controversial. This integrative review seeks to develop a commonly accepted framework to specify the putative clinical phenomena, highlight conflicting issues and discuss ways to challenge each hypothesis and model through adversarial collaboration. The authors agreed on a common framework inspired from systems neuroscience. Specification of DIP, locomotor paratonia (LMP) and psychomotor paratonia (PMP) identified points of disagreement. Some viewed parkinsonian rigidity to be sufficient for diagnosing DIP, while others viewed DIP as a syndrome that should include bradykinesia. Sensitivity of DIP to anticholinergic drugs and the nature of LPM and PMP were the most debated issues. It was agreed that treated SSD should be investigated first. Clinical features of the phenomena at issue could be confirmed by torque, EMG and joint angle measures that could help in challenging the selectivity of DIP to anticholinergics. LMP was modeled as the release of the reticular formation from the control of the supplementary motor area (SMA), which could be challenged by the tonic vibration reflex or acoustic startle. PMP was modeled as the release of primary motor cortex from the control of the SMA and may be informed by subclinical echopraxia. If these challenges are not met, this would put new constraints on the models and have clinical and therapeutic implications.
Online verfügbar: 12. April 2023, Artikelversion: 18. Dezember 2023
Gesehen am 13.05.2024